Contributions to the ecology of hollow dependent saproxylic beetles - Šebek, Pavel (Jihočeská univerzita, 2015)
The thesis consists of two studies contributing to knowledge about the ecology of two model saproxylic species dependent on tree hollows. It includes, firstly, an analysis of the habitat requirements of the violet click beetle, Limoniscus violaceus, and secondly, an analysis of the association of several saproxylic beetles with the presence of the hermit beetle, Osmoderma barnabita, in hollows.
Contributions to the ecology of hollow dependent saproxylic beetles
Keywords: tree cavity; endangered species; Natura 2000; insect ecology; tree cavity; endangered species; Natura 2000; insect ecology